Determination of Intracellular ATP Levels in Mycelium of Fusarium oxysporum - Carmen Ruiz-Roldan; M. Roncero (Bio-Protocol, 2016)
Glycolysis provides metabolites for energy production via oxidative phosphorylation during vegetative growth of Fusarium oxysporum. Therefore, determination of intracellular ATP levels might be of valuable help to analyze regulation of glycolysis/gluconeogenesis pathways. The protocol described here can be applied to other filamentous fungi.